Introducing Theological Interpretation of Scripture - Fandy Handoko Tanujaya (STT Amanat Agung, 2009)
Tinjauan Buku Introducing Theological Interpretation of Scripture: Recovering a Christian Practice. Oleh Daniel J. Treier